Intrathecal dexmedetomidine attenuates mechanical allodynia through the downregulation of brain-derived neurotrophic factor in a mild traumatic brain injury rat model - Soeun Jeon; Jiseok Baik; Jisu Kim; Jiyoon Lee; Wangseok Do; Eunsoo Kim; Hyeon Jeong Lee; Haekyu Kim (Korean Journal of Anesthesiology, 2023)
Background This study evaluated the effects of dexmedetomidine and propofol on brain-derived neurotrophic factor level in the cerebrospinal fluid (c-BDNF) and mechanical allodynia in a mild traumatic brain injury (TBI) rat model. Methods After fixing the rat’s skull on a stereotactic frame under general anesthesia, craniotomy was performed. After impact, 10 µl of drug was injected into the cisterna magna (group S: sham, group D: dexmedetomidine 5 μg/kg, group P: propofol 500 μg/kg, and group T: untreated TBI). The 50% mechanical withdrawal threshold (50% MWT) and c-BDNF level were measured on postoperative days (PODs) 1, 7, and 14. Results The 50% MWT measured on PODs 1, 7, and 14 was lower and the c-BDNF level on POD 1 was higher in group T than in group S. In group D, the c-BDNF level on POD 1 was lower than that in group T and was comparable with that in group S during the whole study period. The 50% MWT of group D was higher than that of group T throughout the postoperative period. In group P, there were no significant differences in the 50% MWT during the entire postoperative period compared with group T; the c-BDNF level was higher than that in group T on POD 1. Conclusions Intrathecal administration of dexmedetomidine may attenuate TBI-induced mechanical allodynia for up to two weeks post-injury through immediate suppression of c-BDNF in mild TBI rats. The inhibition of c-BDNF expression in the acute phase reduced the occurrence of TBI-induced chronic neuropathic pain.